A Computational Study Of Molecular Docking For Antiviral Compounds Against Sars-Cov-2 - Khade Shubham; Dr. Pallavi M. Patil (International Journal of Pharma and Bio Sciences, 2022)
COVID-19 has been the reason for the pandemic, which is induced by the SARS-CoV-2. Potential drugs are being used for its cure, but there's no specific drug for it. To get a specific drug, many drug designing strategies are being used in which molecular docking plays a vital role in computer-assisted drug designing. The aim of this study was to develop an appropriate anti-viral drug against the SARS-CoV-2 virus. In this research, we've tested the molecular docking of Lopinavir (LV), Ritonavir, Zanamivir, Peramivir, Atazanavir, Daclatasvir, Raltegravir on the Receptor Binding Spike proteins of SARS-CoV-2. We further examined it in conjunction with the docking results in response to the recently reported anti-AIDS drugs Lopinavir and ritonavir tablets, which have a poor effect on the treatment of novel coronavirus pneumonia and have toxic side effects. The results of the molecular docking indicate that Raltegravir, an antiviral HIV-drug (-7.68 kcal/mol), had a higher binding affinity than the other medications tested and there is no evidence of Lopinavir or Ritonavir binding completely to major targets such as 2AJF. This docking result suggests that the anti-HIV drug could aid in COVID-19 drug discovery and lopinavir and ritonavir tablets may be ineffective for treating SARS-CoV-2 infections. However, a further study that confirms antiviral activities by in vitro and in vivo evaluation study is required to repurpose these drugs against 2019-nCoV, providing scientists a heads-up on compounds that may be effective.